Rantai Pasok Bunga Krisan Di Kelurahan Kakaskasen II Kecamatan Tomohon Utara Kota Tomohon - Nayoan, Kevin; Lolowang, Tommy F.; Ruaw, Eyverson (Sam Ratulangi University, 2023)
The aim of this research is to describe the flow of the chrysanthemum flower supply chain in Kakaskasen II Village, North Tomohon District, Tomohon City. This research was carried out for three months from November to January 2023. The sampling method used purposive sampling and continued with snowball sampling. The research uses primary data obtained from direct observation and interviews with respondents using questionnaires to farmers, retailers, florists and decorators. So that the total respondents were 17 people. Secondary data was obtained from the Central Bureau of Statistics, and data from the Agriculture Office or BPP of Tomohon District. Secondary data was also obtained from the internet with the topic of this research, namely the chrysanthemum flower supply chain. The analytical method used in this research is descriptive analysis with a qualitative approach. The results of the study show that in the supply chain in Kakaskasen Dua Village, Tomohon District, North of Tomohon City, there are two sources of raw materials, namely from Tomohon breeder farmers and also from the island of Java. The product flow that occurs from farmers to retailers to florists and then to decorators, it changes from cut flower plants to a variety of products such as pot flowers, hand flowers, board flowers, faucets and table flowers. The financial flow that occurs is the opposite of the product flow, that is, from the hairdresser to the farmer. Chrysanthemum flower farmers in the farmer share test are said to be profitable and in the margin test supply chain actors get sufficient or profitable margins. Information flow, the supply chain in Kakaskasen 2 Village has 5 actors, namely farmers - retailers - florists - decorators - consumers.